Analisis Perjanjian Tidak Tertulis Pada Arisan Online Di Kota Cilegon - Mahesa, Nico; Rokilah (LPPM Universitas Ekasakti Padang, 2024)
Online arisan is a new phenomenon in society, attracting various groups. An oral agreement in online arisan serves as a protection of the rights of each party. This study aims to understand the implementation and legal resolution of online arisan agreements in Cilegon City. The research method used is qualitative with a juridical empirical approach. Data were collected through literature studies and interviews. The findings of the research indicate that the implementation of online arisan agreements in Cilegon City does not yet fulfill the valid requirements of an agreement as per Article 1320 of the Indonesian Civil Code (KUHPerdata), and the resolution of issues is conducted non-litigiously as it is considered easier and more efficient. Additionally, this study highlights the importance of using electronic evidence in the dispute resolution process to enhance legal validity and strengthen protection for all parties involved.